S + V + O : Ordres marqués et non marqués en italien - Sandra Augendre (Discours)
The article aims to discuss the notions of marked and unmarked orders, as they are used in the works describing the norms and properties of languages, particularly their grammars. We will focus on the case of Italian, where the construction of the sentence is relatively free, in order to show that claiming there is a canonical or basic structure (SVO for Italian) for descriptive purposes does not reflect the real use which is made of this language. Indeed, the opposition between a basic or unmarked form and its so-called ‘marked’ variants does not seem to fit in a more detailed analysis of linguistic use. We will consider here various types of structures (thematic, syntactic and prosodic) and describe the reasons why, for each of them, one basic form is postulated. We will then try to show that these analyses are valid only for descriptive purposes, and at the sentence level, but that the notions of marked vs unmarked order are no longer relevant at the utterance level, unless a new meaning is attributed to them. As we will show, the concept of marking can be adapted and useful only in relation to the distribution of the utterances and their link with the context.